2016
DOI: 10.1002/ams2.187
|View full text |Cite
|
Sign up to set email alerts
|

Red cell and platelet distribution widths in patients with angina pectoris and acute myocardial infarction

Abstract: Aim: We aimed to determine the relationship of red cell and platelet distribution widths with the onset of acute myocardial infarction, to enable the early detection and prevention of acute myocardial infarction.Methods: Red cell and platelet distribution widths were retrospectively determined in 46 patients with stable angina pectoris and 140 patients with acute myocardial infarction who were brought to the emergency department of our institution. Red cell and platelet distribution widths were determined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Our study revealed that among 211 patients, 181 of them (85.8%) were male and 30 of them (14.2%) were female which is accordance with the results of other studies which report that acute myocardial infarction happens more in men compared to women (16)(17)(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our study revealed that among 211 patients, 181 of them (85.8%) were male and 30 of them (14.2%) were female which is accordance with the results of other studies which report that acute myocardial infarction happens more in men compared to women (16)(17)(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 91%
“…In Gul et al study the age average was 56±13 (18). In another study conducted in Japan the age average was reported to be 66±1 (19). in most performed studies, acute myocardial infarction happened in 60s in majority of patients (20)(21)(22).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The main types of pain are burning pain, squeezing pain, and clamping pain. The duration of pain in patients is generally 3 to 5 minutes, and there is short-term pain within 1 minute [ 18 ]. If the pain is relieved after taking nitroglycerin, it can be diagnosed.…”
Section: Angina Pectoris Treatment and Imaging Analysismentioning
confidence: 99%